The Thr715Pro variant impairs terminal glycosylation of P-selectin - Subramanian, Hariharan; Gambaryan, Stepan; Panzer, Simon; Gremmel, Thomas; Walter, Ulrich; Mannhalter, Christine (Thrombosis and Haemostasis, 2012)
P-selectin variant 715Pro is associated with lower concentrations of plasma P-selectin and reduced risk for thrombosis. We examined the influence of 715Pro on P-selectin synthesis, post-translational processing, surface expression and function using HEK293 cells, which do not express endogenous P-selectin. Mass spectrometry revealed that HEK293 cells produced recombinant P-selectin which has a glycosylation pattern comparable to platelet P-selectin. Compared to wild-type transfectants, 715Pro transfectants have ~50% less terminally glycosylated P-selectin and accumulate more immature P-selectin in Golgi. Following Brefeldin A treatment, the majority of 715Pro P-selectin is not modified by Golgi enzymes, while wild-type P-selectin undergoes complete modification. Flow cytometry revealed that 715Pro transfectants have ~20% less P-selectin on the cell surface compared to wild-type transfectants. Secretion of P-selectin by 715Pro transfectants was about 38% lower compared to wild-type transfectants. Binding of HL-60 cells to 715Pro transfectants was ~29% lower than to wild-type transfectants. This observation was confirmed by the presence of fewer platelet-monocyte aggregates (PMA) in the blood of healthy individuals and patients with angiographically proven atherosclerosis, carrying 715Pro P-selectin compared to individuals with wild-type P-selectin. We conclude that the 715Pro variant impairs terminal glycosylation of P-selectin in Golgi, leading to reduced amounts of mature P-selectin and subsequently less surface expression and secretion of P-selectin. The reduced surface expression of 715Pro P-selectin contributes to inefficient adhesion to HL-60 cells or monocytes.
Keywords: P-selectin; P-selectin polymorphism; P-selectin glycosylation; soluble P-selectin; platelet-monocyte aggregate